2021
DOI: 10.3201/eid2701.203399
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Domestic Swine to Experimental Infection with Severe Acute Respiratory Syndrome Coronavirus 2

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the agent that causes coronavirus disease, has been shown to infect several species. The role of domestic livestock and associated risks for humans in close contact with food production animals remains unknown for many species. Determining the susceptibility of pigs to SARS-CoV-2 is critical to a One Health approach to manage potential risk for zoonotic transmission. We found that pigs are susceptible to SARS-CoV-2 after oronasal inoculation. Among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
99
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(111 citation statements)
references
References 32 publications
8
99
1
3
Order By: Relevance
“…Remarkably, one intranasally inoculated piglet was found positive for viral RNA in the proximal trachea on the day after inoculation ( Vergara-Alert et al, 2020 ). In another in vivo study, inoculation of 10 6 PFU of SARS-CoV-2 simultaneously into the nostrils and the pharynx of 8-week-old American Yorkshire crossbred piglets resulted in mild clinical signs in at least 5 out of 19 animals ( Pickering et al, 2021 ). Ocular discharge, nasal secretion and cough were observed within the first days after infection, but body temperature remained normal.…”
Section: Livestock Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, one intranasally inoculated piglet was found positive for viral RNA in the proximal trachea on the day after inoculation ( Vergara-Alert et al, 2020 ). In another in vivo study, inoculation of 10 6 PFU of SARS-CoV-2 simultaneously into the nostrils and the pharynx of 8-week-old American Yorkshire crossbred piglets resulted in mild clinical signs in at least 5 out of 19 animals ( Pickering et al, 2021 ). Ocular discharge, nasal secretion and cough were observed within the first days after infection, but body temperature remained normal.…”
Section: Livestock Animalsmentioning
confidence: 99%
“…In addition, infectious virus was isolated 13 days after infection from the submandibular lymph node of a sacrificed pig. Two other pigs tested positive for serum antibodies and anti-SARS-CoV-2 antibodies were also detected in saliva recovered from chewing-ropes ( Pickering et al, 2021 ).…”
Section: Livestock Animalsmentioning
confidence: 99%
“…Studies on pigs are inconsistent. While previous studies [ 41 , 49 ] found that pigs seem to be resistant to SARS-CoV-2 infection and are unlikely to be a SARS-CoV-2-carrier animal species, a recent experimental infection contradicted these findings, suggesting that infectious dose and host-related factors could influence the experimental outcome [ 50 ].…”
Section: Case Studies In the Context Of Sars-cov-2mentioning
confidence: 99%
“…Structural analysis of the interaction has been reported [ 50 , 66 ], whilst others have used an antibody approach to study this interaction [ 67 ]. Based on such data from several groups [ 36 , 38 , 48 , 63 , 64 ], lists of such amino acids have been created ( Table 2 ). Damas et al [ 41 ] highlight 25 amino acids across the 805 residues in the sequence.…”
Section: Sequence Analysismentioning
confidence: 99%
“…The USDA keep a database [ 35 ] of the animals found to be positive for the virus in the United States of America, and at the time of writing there were 11 tigers, 3 lions, 3 snow leopards, one cougar, 67 cats, 46 dogs, 3 gorillas and 16 mink listed. Recently it has been reported that pigs ( Sus scrofa domesticus ) are susceptible following oronasal inoculation [ 36 ]. Sixteen animals were tested, with viral RNA detected from the nasal wash and oral fluids from two animals and live virus from one.…”
Section: Introductionmentioning
confidence: 99%